Dampak Pandemi Covid-19 terhadap Bisnis Online Shop (Baju Anak-Anak) di Kota Serang - Hidayat, Syarif (Mabsya: Jurnal Manajemen Bisnis Syariah, 2021)
This study aims to find out and analyze the impact of the COVID-19 pandemic on online shop businesses in the city of Serang. The research method used is descriptive qualitative method, using sources from informants. The process of selecting key informants rolled like a snowball. The research time is March to June 2021. Data collection techniques use field observations, interviews with research objects, and documentation as research supporting materials. The research locus is in Serang City. The results of the study found that the impact of the Covid-19 pandemic on the online shop business was a decline in sales because consumers were now more focused on buying basic necessities and medicines for health.